Can argillaceous formations isolate nuclear waste? Insights from isotopic, noble gas, and geochemical profiles. Issue 3 (23rd February 2015) - Hendry, M. J.; Solomon, D. K.; Person, M.; Wassenaar, L. I.; Gardner, W. P.; Clark, I. D.; Mayer, K. U.; Kunimaru, T.; Nakata, K.; Hasegawa, T.
Abstract There is considerable interest in the use of thick argillaceous geologic formations to contain nuclear waste. Here, we show that diffusion can be the controlling transport process in these formations and diffusional time scales for δ18O and δ2H in water, dissolved He, and Cl transport in shale‐dominated aquitards are typically over 106 years, well exceeding the regulatory requirements for isolation in most countries. Our scientific understanding of diffusive solute transport processes through argillaceous formations would benefit from the application of additional isotopic tracers (e.g., using new 4He sampling technology), multidimensional diffusive‐dispersive modeling of groundwater flow and diffusive‐dispersive solute transport over long geologic time scales, and an improved understanding of spatial heterogeneity as well as time‐dependent changes in the subsurface conditions and properties of argillaceous formations in response to events such as glaciation. Based on our current isotopic and geochemical understanding of transport, we argue that argillaceous formations can provide favorable long‐term conditions for isolating nuclear wastes.